Exploring Genes and Phenotypes Within Chromosomal Regions Using OMIM's GeneScout. Issue 9 (21st September 2022) - Applegate, Carolyn D.; Schiettecatte, François; Hamosh, Ada; Amberger, Joanna S.
Abstract: Structural variation in genomes, such as copy number variants (CNVs), is under scrutiny for its contribution to phenotypic expression and evolution. Regions of homozygosity (ROH) are ripe for phenotype‐gene discovery. Determining the genes and related phenotypes within genomic regions is key to studying potential functional and phenotypic consequences. Because individuals have multiple CNVs and ROHs in their genome, identifying genomic regions that are phenotypically significant is challenging. GeneScout is a web‐based tool that can be used to search genomic regions to display and filter the genes and their associated phenotypes within regions of interest. Phenotypes and their associated gene(s) can then be filtered to show only the genes with phenotypes that have a particular inheritance pattern and/or specific clinical feature(s). Phenotypes can then be selected to compare the clinical synopses side‐by‐side in Online Mendelian Inheritance in Man (OMIM ® ). Additionally, two coordinate sets can be compared to determine either the regions of overlap or the unique regions (subtraction). The resulting coordinate ranges are displayed on the results page, and the results table displays only the genes and phenotypes present within the coordinate ranges. The interactive table includes gene‐specific links to external resources such as ClinVar, ClinGen validity, ClinGen dosage, and gnomAD, and a diamond symbol next to the gene name indicates a gene that spans the start or end of a coordinate range. Searches and comparisons may be performed for coordinates in assemblies GRCh37 (hg19) and GRCh38 (hg38). The results page offers the option to liftover coordinates entered in GRCh37 to GRCh38 and updates the results table to display the gene content based on assembly GRCh38. The search coordinates and results table can be downloaded in a tab‐delimited or Excel file. © 2022 Wiley Periodicals LLC. Basic Protocol : Searching GeneScout